CORRELATION BIOFILM WITH INFECTION: IMPLICATIONS FOR PUBLIC HEALTH AND STRATEGIES TO CONTROL - Purbowati, Rini (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2016)
Biofilms are formed in the surfaces of mucosal of the body cavity can be a major source of infection . Infection by microbial biofilm formers are difficult to treat because of their greater resistance to antimicrobial agents than individual cells . Therefore biofilm -related infections and increased the economic burden of the country. The purpose of this literature review is to examine literature on biofilms and biofilm-associated microbes and their contribution to the disease burden of man with the aim of drawing attention to their public health implication.Biofilm are defined as âcollections of microorganisms and their associated extracellular products at an interface and generally attached to a biological and non-biological substratum. Biofilm formation are influenced by factors controlling cell attachment, nature of surface, propertis of medium, and properties of the microbial cell surface. The ability of biofilm formation is genetically regulated by ica ABDC operon. Biofilm life cycle include adhesion of cells, formation of microcolonies, formation of biofilm and detachment anddispersal of biofilm. Structure of biofilm consists microorganisms and extracellular polymeric substances with vertical structures of microorganisms sometimes take the form of towers or mushrooms which are separated by interstitial spaces. Bacterial biofilm showed increased resistance to antibiotics, disinfectants and resistant to phagocytosis and other mechanisms of innate and adaptive immune system. Biofilms associated with food borne illness and affect to food security. Biofilms have been implicated in a wide variety of microbial infections in the body such as as urinary tract infections, catheter infections, middle-ear infections, formation of dental plaque, gingivitis, legionellosis ,infections involving contact lenses, and less common but more lethal processes such as endocarditis, infections in cystic fibrosis, and infections of permanent indwelling devices such as joint prostheses and heart valves. It is important for government agencies with a mandate for safeguarding public health and environment to develop and adopt ap propriate health risk assessment and biofilm-specific guidelines that are protective of both public health and the environment.